The Legal Nature of Futures Contracts in Commodity Exchanges in Jordanian Legislation - Al-Amawi, Dr. Mohammed Ali (International Journal of Membrane Science and Technology, 2023)
Legal jurisprudence tends to classify futures settlement contracts in commodity exchanges as speculative and betting contracts, based on cash settlement as one of the methods for settling futures contracts. Sometimes, these contracts are settled by the difference between the opening and closing prices over a specified period. Such classification is a limited perspective based on legal jurisprudence viewing futures contracts as ordinary sales contrary to reality. Settlement futures contracts in commodity exchanges are distinctive contracts, and their uniqueness is derived from the nature of the assets traded. These contracts involve essential commodities that play a crucial role in national economies. Moreover, they are subject to a specific legal framework that differs from the legal system governing ordinary contracts. These contracts serve various purposes beyond buying and selling for immediate consumption and trade. They function as financial instruments for investment and risk management, serving purposes beyond simple consumption and immediate trade. The essential distinction that has led to confusion about futures settlement contracts is the time gap between their formation and execution, unlike ordinary contracts that are immediately executed.In this study, we attempted to unveil the ambiguity surrounding futures settlement contracts in commodity exchanges by highlighting their true nature as financial instruments playing a significant role in national economies. This reality has given futures settlement contracts a distinct legal nature.